A New Chaotic System with a Pear-shaped Equilibrium and its Circuit Simulation - Aceng Sambas; Sundarapandian Vaidyanathan; Mustafa Mamat; Muhammad Afendee Mohamed; Mada Sanjaya WS (Institute of Advanced Engineering and Science, 2018)
This paper reports the finding a new chaotic system with a pear-shaped equilibrium curve and makes a valuable addition to existing chaotic systems with infinite equilibrium points in the literature. The new chaotic system has a total of five nonlinearities. Lyapunov exponents of the new chaotic system are studied for verifying chaos properties and phase portraits of the new system are unveiled. An electronic circuit simulation of the new chaotic system with pear-shaped equilibrium curve is shown using Multisim to check the model feasibility.